The impact of cultural values on green purchase intentions through ecological awareness and perceived consumer effectiveness: An empirical investigation - Hussain, Shahbaz; Huang, Jinyan (Frontiers in Environmental Science, 2022)
The findings of a quantitative study about Chinese consumers regarding how cultural values, environmental awareness, and perceived consumer effectiveness (PCE) influence their green purchase intentions are presented in this article. This study aimed to explain these crucial factors’ direct and indirect effects on green purchases and the impact of cultural values and environmental awareness on PCE. Specifically, a conceptual model was suggested and empirically tested using survey information gathered from 371 customers from China and SmartPLS-SEM approach was applied. The results indicated that PCE significantly influences consumers’ intentions to make green purchases, and through environmental awareness and PCE, cultural values, directly and indirectly, influence Chinese consumers’ green buying intentions. This study offers novel perspectives on consumer behavior for purchasing environment-friendly products.